EcoPhilosophy in the thought of Heidegger and Deleuze/Guattari - Calmon Modenesi, Jean (Geografares, 2021)
This article was written from our Post-Doctoral research, whose title is EcoPhilosophy: Heidegger and Deleuze/Guattari - virtual dialogue, completed in 2020. In this research, we tried to demonstrate the hypothesis according to which EcoPhilosophy is a concept that underlies both the thinking of Martin Heidegger and that of Gilles Deleuze and Félix Guattari. This means that the concept of EcoPhilosophy is the unthinkable thought of such thinkers. Here, the unthought does not mean the no thought, but the thought, which, however, was not properly enunciated by them. Hence why this research was most justified, namely, to enunciate the concept of EcoPhilosophy as thought, on the one hand, by the German thinker, and, on the other, by the pair of French thinkers. But precisely by enunciating the concept of EcoPhilosophy in the thought of both Heidegger and the duo Deleuze and Guattari, we also contributed to its creation - a collective conceptual creation.